Fra norma e cura. Madri e padri nel secolo dei lumi - Carmela Covato (LED Edizioni Universitarie, 2010)
Between Provisions and Care. Mothers and Fathers in the Age of the Enlightenment This contribution fits in with a relatively recent research path that aims to reconstruct the history of educational relations by also taking social diversity and the gender roles of the subjects concerned into account, in the light of the great deal of historiographical material aiming to give substance to entities that are often considered in an abstract and symbolic manner, even within a long obsolete pedagogical tradition. This work particularly dwells on the debate carried on between the 18th and 19th century in the history of western culture with respect to the social role of motherhood, considered by intellectuals and politicians as a value to be rediscovered in order to avoid, amongst other things, the damage caused by a high child mortality rate. The Enlightenment tradition, and more specifically the thinking of Jean-Jacques Rousseau, forms the basis for a new paradigm of childhood charged with the redeeming task of regenerating humankind and that is linked to a view of motherhood exalted in its immutable naturalness. What tends to emerge is a bourgeois view of female identity that is triumphant at the symbolic level in 19th century religious, pedagogical and juridical percepts, but becomes a moral constraint for women and may thus be considered as antithesis to every form of intellectual and social emancipation. While, for women, being a mother would increasingly be considered a duty, for some men «of exception» being a loving father would mean a new kind of yearning and a «place» of utopian thinking.